Hierarchical graphene oxide-Ni3S2 quantum dots nanocomposites modified glassy carbon electrode for electrochemical detection of dopamine and tyrosine - Annapragada, Ratnamala; Mohammad, Haseena; Mohammad, Noorjahaan; Gavini, Deepti R.; Begum, Gousia (Frontiers in Materials, 2023)
A facile synthetic strategy is demonstrated to generate nickel sulfide quantum dots (Ni3S2). The thus formed Ni3S2 quantum dots are assembled onto exfoliated graphene oxide sheets hydrothermally to form nickel sulfide-graphene oxide nanocomposite material (GO-Ni3S2). The microscopic and spectroscopic characterization of the GO-Ni3S2 nanocomposites revealed the shape, size, crystalline phases, and oxidation states (of elements) of the hybrid material. The GO-Ni3S2 nanocomposites are then coated onto the glassy carbon electrode by drop casting to form